Aggregation-induced luminescence magnetically encoded microspheres based on in-situ polymerization coating and preparation method and application thereof

By embedding AIE molecules inside the microspheres and depositing magnetic particles on the surface, the problem of insufficient coding capabilities of quantum dots and organic materials is solved, and efficient magnetic fluorescence encoded microspheres are achieved, improving the encoding capacity and stability, and making biochip New material strategies are provided.

CN118185622BActive Publication Date: 2025-01-07AIE INSTITUTE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410136757.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-31
Publication Date
2025-01-07
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

In the prior art, the encoding capability of quantum dot-encoded microspheres is limited by the reabsorption and color-split effect between fluorescence signals. Traditional organic materials experience fluorescence quenching in aggregation state, which limits the encoding capacity and stability, and lacks Highly efficient magnetic fluorescent encoded microsphere material.

Method used

Using aggregation-induced luminescence (AIE) magnetically encoded microspheres based on in situ polymerization, embedded in the blank polymer microspheres through in situ polymerization of AIE molecules, and magnetic particles are deposited on the surface of the microspheres, using the in situ of iron salts. The precipitation method generates magnetic particles, and the amount of AIE molecules and iron salts is regulated to achieve encoded microspheres with uniform particle size and strong fluorescence uniformity.

Benefits of technology

Improve the encoding capacity and detection stability of magnetically encoded microspheres, and achieve a single wavelength high encoding capacity of 10 or more. The simple preparation method enables AIE molecules to be effectively applied to encoded microspheres, providing a new strategy for protein biochips. Core raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118185622B_ABST
    Figure CN118185622B_ABST
Patent Text Reader

Abstract

The invention discloses an aggregation-induced luminescence magnetic coded microsphere based on in-situ polymerization coating and a preparation method and application thereof; the aggregation-induced luminescence magnetic coded microsphere comprises an AIE polymer microsphere and a magnetic particle; the AIE polymer microsphere is obtained by embedding an AIE molecule in a blank polymer microsphere through an in-situ polymerization coating method, and the amount of the AIE molecule in the in-situ polymerization coating method is 0.01-10wt% of the amount of the blank polymer microsphere; the magnetic particle is deposited on the surface of the AIE polymer microsphere through an in-situ precipitation method of an iron salt, and the amount of the iron salt in the in-situ precipitation method is 3-30wt% of the amount of the blank polymer microsphere. The CV value of the flow fluorescence signal and the CV value of the flow FCS of the aggregation-induced luminescence magnetic coded microsphere of the invention are both less than 10%, and the coding peak is ≥10; an important fluorescent material is added to the coding element, and a new strategy is provided for the core raw materials of the protein biochip.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of in vitro diagnosis, and in particular relates to an aggregation-induced luminescence magnetic coded microsphere based on in-situ polymerization coating, and a preparation method and application thereof. Background Art

[0002] The development and completion of the human genome and proteome in recent years has led to a huge demand for large-scale analysis of biomolecules, which has promoted the rapid development of liquid suspension biochips with encoded microspheres as the core. Liquid suspension biochips with rapid high-throughput flow cytometry and magnetic separation as analytical methods have gradually become a new goal for accurate diagnosis by performing rapid and high-throughput multiplex detection of markers such as proteins, nucleic acids and small molecules. Among them, the development of encoded microspheres with high encoding capacity and stability is still a huge challenge. The design of suitable encoded microspheres has the following requirements: high photostability, good anti-magnetism, large number of codes, no reabsorption and crosstalk effects, etc.

[0003] Spectral signals are widely used in the construction of liquid biochips due to their flexible encoding and fast decoding speed. At present, the commonly used spectral encoding materials are mainly organic materials, quantum dots, upconversion dots and photonic crystals, etc. Quantum dots have become popular encoding materials due to their high brightness and narrow emission spectrum, but the encoding ability of quantum dots is limited by the reabsorption and cross-color effect between quantum dot fluorescence signals, which limits the application of quantum dot encoding microspheres.

[0004] At present, commercial liquid biochip Luminex system and BD's cytometric bead array all use organic dyes for encoding, but traditional organic materials have fluorescence quenching in the aggregated state, which limits the encoding capacity and stability of traditional organic materials. The new aggregation-induced emission (AIE) material discovered by the team of Academician Tang Benzhong in 2001 is a promising encoding material for the preparation of encoded microspheres, because AIE materials can achieve in-situ enhancement of fluorescence signals during the aggregation process. Aggregation-induced emission materials have properties such as large Stokes shift, strong resistance to photobleaching, and anti-magnetism, and are an excellent encoding microsphere material. However, there are few public reports on the efficient preparation of magnetic fluorescence encoding using AIE materials. Therefore, it is very necessary to develop an aggregation-induced emission magnetic encoding microsphere with uniform particle size, strong fluorescence uniformity and strong encoding ability. Summary of the invention

[0005] In order to solve the shortcomings of the prior art, the present invention aims to provide an aggregation-induced emission (AIE) magnetically encoded microsphere based on in situ polymerization coating and a preparation method and application thereof. The aggregation-induced emission magnetically encoded microsphere has the characteristics of large Stokes shift, high fluorescence intensity and high encoding capacity.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] Aggregation-induced luminescence magnetically encoded microspheres based on in-situ polymerization and coating, including AIE polymer microspheres and magnetic particles;

[0008] The AIE polymer microspheres are obtained by embedding AIE molecules inside blank polymer microspheres through an in-situ polymerization coating method, and the amount of AIE molecules used in the in-situ polymerization coating method is 0.01-10wt% of the amount of the blank polymer microspheres;

[0009] The magnetic particles are deposited on the surface of the AIE polymer microspheres by an in-situ precipitation method of iron salts, wherein the amount of iron salts used in the in-situ precipitation method is 3-30 wt % of the amount of blank polymer microspheres used.

[0010] Preferably, the blank polymer microspheres are selected from at least one of polystyrene microspheres, polymethyl methacrylate microspheres and polyglycidyl acrylate microspheres;

[0011] Further preferably, the blank polymer microspheres are selected from polystyrene microspheres or polyglycidyl acrylate microspheres.

[0012] Preferably, the magnetic particles are Fe 3 O 4 ;

[0013] Preferably, the iron salt is selected from at least one of a trivalent iron salt and a divalent iron salt; further preferably, the trivalent iron salt is selected from at least one of ferric chloride hexahydrate and anhydrous ferric chloride; the divalent iron salt is selected from at least one of ferrous chloride tetrahydrate, ferrous chloride dihydrate, ferrous sulfate and ferrous sulfate heptahydrate;

[0014] Further preferably, considering the uniformity of magnetic particles deposited on the surface of the AIE polymer microspheres, the iron salt is a compound of a trivalent iron salt and a divalent iron salt, and the mass amount of the trivalent iron salt is 10% to 60% of the mass amount of the divalent iron salt.

[0015] Preferably, the AIE molecule is selected from at least one of the following AIE-1 molecules to AIE-16 molecules:

[0016]

[0017]

[0018] Alkyl chain in AIE-1 molecule -C 8 H 17 Each is independently a branched chain alkyl or a straight chain alkyl.

[0019] Alkyl chain in AIE-11 molecule -C 6 H 13Each is independently a branched chain alkyl or a straight chain alkyl.

[0020] Preferably, the in-situ polymerization coating method is to cause the AIE molecules, reactive monomers, initiators and crosslinkers to undergo swelling polymerization reaction with blank polymer microspheres in the dispersed phase of the reaction system so that the AIE molecules are embedded inside the blank polymer microspheres;

[0021] Further preferably, in the in-situ polymerization coating method, the reactive monomer is selected from at least one of styrene, glycidyl methacrylate and isocyanoethyl methacrylate, the initiator is selected from at least one of azobisisobutyronitrile (AIBN), dibenzoyl peroxide, azobisisovaleronitrile, cumene hydroperoxide and azobisisoheptylonitrile, the cross-linking agent is selected from at least one of divinylbenzene, ethylene glycol dimethacrylate, diisocyanate and N,N-methylenebisacrylamide; the particle size range of the blank polymer microspheres is 0.03 μm to 50 μm.

[0022] More preferably, the particle size of the blank polymer microspheres ranges from 0.5 μm to 20 μm. The initiator is selected from azobisisobutyronitrile or dibenzoyl peroxide. The crosslinker is selected from divinylbenzene or ethylene glycol dimethacrylate.

[0023] Further preferably, in the in-situ polymerization coating method, the mass amount of the AIE molecule is 0.001% to 10% of the mass amount of the reactive monomer, the mass amount of the initiator is 0.1% to 10% of the mass amount of the reactive monomer, and the mass amount of the cross-linking agent is 1% to 50% of the mass amount of the reactive monomer.

[0024] Preferably, the in-situ precipitation method is to add an alkaline solution to react with the iron salt chelated on the surface of the AIE polymer microspheres in situ to generate magnetic particles that are deposited on the surface of the AIE polymer microspheres.

[0025] Further preferably, in the in-situ precipitation method, the surface of the AIE polymer microspheres is modified by sulfonation, and the alkaline solution is selected from at least one of sodium hydroxide solution, ammonia water, potassium hydroxide solution and sodium bicarbonate solution;

[0026] Preferably, the CV value of the flow fluorescence signal and the CV value of the flow FCS of the aggregation-induced luminescence magnetic encoding microspheres based on in-situ polymerization coating are both less than 10%, and the encoding peak is ≥10-fold.

[0027] The above-mentioned method for preparing aggregation-induced luminescence magnetically encoded microspheres based on in-situ polymerization coating comprises the following steps:

[0028] S1. Preparation of AIE polymer microspheres by in situ polymerization and coating

[0029] Dispersing blank polymer microspheres in water, adding a swelling agent to swell the microspheres to obtain a microsphere dispersion;

[0030] AIE molecules, initiators and crosslinkers are dissolved in reactive monomers, and microsphere dispersion is added. After swelling reaction, stabilizers are added, and the swelling agent is removed by heating. The supernatant is removed by centrifugation to obtain AIE polymer microspheres.

[0031] S2. Preparation of Aggregation-Induced Luminescence Magnetic Encoded Microspheres Based on In-situ Polymerization and Coating by In-situ Precipitation

[0032] The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is increased for reaction, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation-modified surfaces. The microspheres are mixed with iron salt and water for reaction, and the supernatant is removed by centrifugation to obtain iron salt-chelated AIE polymer microspheres. An alkaline solution is added, and the temperature is increased. The iron salt reacts in situ to generate magnetic particles that are deposited on the surface of the AIE polymer microspheres. The supernatant is removed by centrifugation to prepare aggregation-induced luminescence magnetically encoded microspheres based on in situ polymerization coating.

[0033] Preferably, the method for preparing the aggregation-induced luminescence magnetically encoded microspheres based on in-situ polymerization coating comprises the following steps:

[0034] S1. Preparation of AIE polymer microspheres by in situ polymerization and coating

[0035] Dispersing blank polymer microspheres in water, adding a swelling agent to swell the microspheres for 0.1 to 6 hours to obtain a microsphere dispersion;

[0036] AIE molecules, initiators and crosslinkers are dissolved in reactive monomers, and microsphere dispersion is added. After swelling reaction for 0.5 to 6 hours, a stabilizer is added, and the temperature is raised to 60°C to 100°C for reaction for 2 to 12 hours to remove the swelling agent, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres.

[0037] S2. Preparation of Aggregation-Induced Luminescence Magnetic Encoded Microspheres Based on In-situ Polymerization and Coating by In-situ Precipitation

[0038] The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is increased to 30°C to 100°C and the reaction is carried out for 4 to 12 hours, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation modified on the surface. The microspheres are mixed with iron salt and water, and the mixture is immersed in the solution for reaction for 0.5 to 10 hours, and the supernatant is removed by centrifugation to obtain iron salt-chelated AIE polymer microspheres. An alkaline solution is added, and the temperature is increased to 40°C to 120°C and the reaction is carried out for 0.5 to 4 hours. The iron salt reacts in situ to generate magnetic particles which are deposited on the surface of the AIE polymer microspheres, and the supernatant is removed by centrifugation to prepare aggregation-induced luminescence magnetically encoded microspheres based on in situ polymerization coating.

[0039] Further preferably, in step S1, the time for removing the swelling agent is 2 hours to 10 hours. More preferably, the time for removing the swelling agent is 4 hours and the temperature is 80°C.

[0040] Further preferably, in step S2, the soaking reaction time is 2 to 4 hours; and the reaction temperature after adding the alkaline solution is 60° C. to 80° C.

[0041] Preferably, in step S1, the mass amount of blank polymer microspheres in the microsphere dispersion is 0.1% to 20% of the mass amount of water, and the mass amount of the swelling agent is 0.05% to 40% of the mass amount of water; the swelling agent is selected from at least one of dichloromethane, tetrahydrofuran, chloroform, anisole, benzyl alcohol and toluene;

[0042] More preferably, the mass amount of blank polymer microspheres in the microsphere dispersion is 0.5% to 10% of the mass amount of water. The swelling agent is selected from dichloromethane, tetrahydrofuran or toluene.

[0043] Preferably, in step S1, the mass amount of the stabilizer is 0.01% to 5% of the mass amount of water; the stabilizer is selected from at least one of polyvinyl pyrrolidone and polyvinyl alcohol;

[0044] Preferably, in step S2, the mass concentration of the sulfuric acid solution is 70% to 99%; the mass amount of the AIE polymer microspheres is 1% to 30% of the mass amount of the sulfuric acid solution;

[0045] Further preferably, the mass concentration of the sulfuric acid solution is 98.3%; and the mass amount of the AIE polymer microspheres is 5% to 20% of the mass amount of the sulfuric acid solution.

[0046] Preferably, in step S2, the mass dosage of the iron salt is 0.0005% to 25% of the mass dosage of water; the mass dosage of the alkaline solution is 0.1% to 50% of the mass dosage of water; the mass concentration of the alkaline solution is 1% to 10%;

[0047] Preferably, the water in step S1 and step S2 is ultrapure water; the centrifugal speed is 3000 rpm to 6000 rpm, the centrifugal time is 5 min to 60 min, and the number of centrifugation is more than three times.

[0048] More preferably, the centrifugal speed is 4000 rpm to 6000 rpm, the centrifugal time is 5 min to 20 min, and the number of centrifugation is three times.

[0049] The above-mentioned aggregation-induced luminescence magnetically encoded microspheres based on in situ polymerization coating are used in in vitro non-disease diagnostic detection.

[0050] The present invention proposes a new technology for in-situ polymerization embedding technology and in-situ generation to efficiently prepare aggregation-induced emission (AIE) magnetically encoded microspheres. AIE molecules are embedded into the interior of the microsphere matrix by in-situ polymerization, and magnetic particles are generated on the surface of the microspheres by an in-situ generation method of iron salts. At the same time, by regulating the dosage of AIE molecules and iron salts, single-wavelength aggregation-induced emission magnetically encoded microspheres with uniform particle size and strong fluorescence uniformity and high encoding capacity are obtained. The microspheres have excellent detection stability and can achieve 10 or more encodings.

[0051] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:

[0052] (1) Compared with the fluorescent materials of traditional magnetic encoded microspheres, the AIE materials of the aggregation-induced luminescence magnetic encoded microspheres based on in situ polymerization coating of the present invention improve the encoding capacity of the magnetic encoded microspheres and solve the problem that traditional fluorescent materials are easily quenched under magnetic matrices. Even in high magnetic content microspheres, the single-wavelength AIE encoding capacity can reach 10-fold capacity.

[0053] (2) The present invention uses simple in situ polymerization embedding and in situ generation technology to encapsulate hundreds of millions of AIE molecules inside the microspheres, and deposits magnetic particles in situ on the surface of the microspheres. By adjusting the amount of AIE molecules and iron salts, AIE magnetic fluorescent encoded microspheres with optimal performance are obtained.

[0054] (3) The in-situ polymerization-coated aggregation-induced emission magnetic encoded microspheres of the present invention have typical aggregation-induced emission properties. The AIE molecules are embedded in the interior of the microspheres and can emit strong fluorescence in the aggregates. At the same time, the strong photostability of the AIE material itself provides excellent detection stability.

[0055] (4) The preparation method of the aggregation-induced luminescence magnetic encoded microspheres based on in situ polymerization coating of the present invention is simple, realizes the effective application of AIE molecules in the preparation of encoded microspheres, adds an important fluorescent material to the encoding element, and provides a new strategy for the core raw materials of protein biochips. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is a scanning electron microscope image of the aggregation-induced luminescence magnetically encoded microspheres prepared in Example 1.

[0057] Figure 2 Schematic diagram of flow encoding of aggregation-induced luminescence magnetically encoded microspheres prepared in Example 1. DETAILED DESCRIPTION

[0058] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0059] The blank polymer microspheres in the examples and comparative examples are polystyrene polymer microspheres with a diameter of 3 μm, which are from AIE Research Institute and have a product number of NWKPB-300.

[0060] The room temperature in the examples and comparative examples was 25°C.

[0061] The encoding data of the aggregation-induced luminescence magnetically encoded microspheres were tested using an analytical flow cytometer. The CV value of the flow fluorescence signal represented the uniformity of the fluorescence swelling, and the CV value of the flow FCS represented the uniformity of the particle size of the microspheres. According to the detection performance requirements of in vitro diagnostics, the CV value of the flow fluorescence signal and the CV value of the flow FCS must be less than 10% to determine that the encoding was successful, otherwise it failed.

[0062] Example 1

[0063] Weigh 1 g of blank polymer microspheres and disperse them in 100 g of water. Add 2 mL of dichloromethane and swell for 30 min to obtain a microsphere dispersion.

[0064] 10 mg of AIE-1 molecules (alkyl chain-C 8 H 17 The AIE polymer microspheres were added to 50 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was repeated three times to obtain the AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was repeated three times to obtain the AIE polymer microspheres with sulfonation modification on the surface.

[0065] Ferrous sulfate heptahydrate and ferric chloride hexahydrate were mixed with 100g water in a mass ratio of 2:1 (the total mass of iron salt accounted for 10wt% of the mass of blank polymer microspheres), and the above-obtained AIE polymer microspheres with sulfonated surface were added. After soaking and reacting for 1h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain iron salt-chelated AIE polymer microspheres. 50mL of 1mol / L sodium hydroxide solution was added, the temperature was raised to 80℃, and the reaction was carried out for 2h. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres. The microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0066] The morphology of the aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 4.5 μm (e.g. Figure 1 ). The CV value of the flow fluorescence signal tested by analytical flow cytometer was 3.5%, the CV value of flow FCS was 6.6%, the encoding peak was 10-fold, and the encoding was successful ( Figure 2 ).

[0067] Example 2

[0068] The preparation method and test of aggregation-induced luminescence magnetically encoded microspheres in this embodiment are different from those in Example 1 only in that the total mass of the iron salt accounts for 30 wt % of the mass of the blank polymer microspheres; the rest are the same.

[0069] The CV value of the flow fluorescence signal tested by analytical flow cytometer was 4.5%, the CV value of flow FCS was 3.4%, the encoding peak was 10-fold, and the encoding was successful.

[0070] Comparative Example 1

[0071] Fluorescein-1 (FITC) was selected as the fluorescent material, and the preparation method of the encoded microspheres was consistent with that in Example 1 above. The encoding data of the fluorescein magnetic encoded microspheres was tested using an analytical flow cytometer. Due to the aggregation-induced luminescence quenching effect of fluorescein, there was no enhancement effect on the ratio of the fluorescence intensity before and after fluorescent embedding. The CV value of the tested flow fluorescence signal was 23.8%, and the CV value of the flow FCS was 11.8%, indicating encoding failure.

[0072] Comparative Example 2

[0073] Quantum dots-1 (CdS / ZnS) were selected as the fluorescent material. The preparation method of the encoded microspheres was consistent with that in Example 2. The encoding data of the quantum dot magnetic encoded microspheres were tested using an analytical flow cytometer. Due to the weak antimagnetism of the quantum dots, there was no obvious change in the intensity before and after the fluorescence coating. The CV value of the tested flow fluorescence signal was 7.3%, and the CV value of the flow FCS was 18.5%, indicating that the encoding failed.

[0074] Comparative Example 3

[0075] The fluorescent material is a rare earth ion complex (Eu), and the preparation method of the coded microspheres is consistent with the above-mentioned Example 1. The coding data of the rare earth ion magnetic coded microspheres is tested using an analytical flow cytometer. Due to the poor stability of the rare earth ion signal, the uniformity of the fluorescent coating cannot be guaranteed. The CV value of the tested flow fluorescence signal is 34.3%, and the CV value of the flow FCS is 12.5%, and the coding fails.

[0076] Comparative Example 4

[0077] The fluorescent material is AIE-1 (alkyl chain-C 8 H17 The preparation method of the encoded microspheres is consistent with that of Example 1, except that the total mass of the iron salt accounts for 40wt% of the mass of the blank polymer microspheres. The encoding data of the aggregation-induced luminescence magnetic encoded microspheres were tested using an analytical flow cytometer. Due to the excessively high amount of total iron salt added during the preparation process and the quenching effect of magnetism on fluorescence, the uniformity of the particle size and the uniformity of the fluorescent coating could not be guaranteed. The CV value of the tested flow fluorescence signal was 22.5%, and the CV value of the flow FCS was 20.6%, indicating encoding failure.

[0078] The encoding data of the magnetically encoded microspheres of Examples 1-2 and Comparative Examples 1-4 are shown in Table 1.

[0079] Table 1 Effects of different fluorescent material types and iron salt dosage on streaming coding results

[0080]

[0081] Example 3

[0082] Weigh 0.5 g of blank polymer microspheres and disperse them in 50 g of water. Add 1 mL of dichloromethane and swell for 30 min to obtain a microsphere dispersion.

[0083] 5mg AIE-3 molecules, 30mg AIBN, and 2g divinylbenzene were dissolved in 2.5mL styrene (the mass of AIE molecules accounted for 1wt% of the mass of blank polymer microspheres), and the microsphere dispersion was added; after swelling at room temperature for 6h, 100mg polyvinyl pyrrolidone was added, the temperature was raised to 70°C, and the reaction was continued for 12h; the microspheres were centrifuged at 5000rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 30mL concentrated sulfuric acid (98.3wt%), the temperature was raised to 80°C, and the reaction was continued for 8h; the microspheres were centrifuged at 5000rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface.

[0084] A total mass of 0.1 g of ferrous sulfate heptahydrate and ferric chloride hexahydrate was mixed with 100 g of water in a mass ratio of 2:1 (the total mass of iron salts accounted for 20 wt% of the mass of blank polymer microspheres), and the above-obtained AIE polymer microspheres with sulfonated surfaces were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain iron-chelated AIE polymer microspheres. 30 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salts reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres. The microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0085] The morphology of the aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 4.5 μm. The CV value of the flow fluorescence signal tested by an analytical flow cytometer was 2.5%, the CV value of the flow FCS was 3.6%, and the encoding peak was 10-fold, indicating successful encoding.

[0086] Example 4

[0087] Weigh 1 g of blank polymer microspheres and disperse them in 75 g of water. Add 2 mL of dichloromethane and swell for 30 min to obtain a microsphere dispersion.

[0088] 5mg AIE-5 molecules, 50mg AIBN, and 2g ethylene glycol dimethacrylate were dissolved in 5mL poly(glycidyl methacrylate) (the mass of AIE molecules accounted for 0.5wt% of the mass of blank polymer microspheres), and the microsphere dispersion was added; after swelling at room temperature for 6h, 100mg polyvinyl pyrrolidone was added, the temperature was raised to 70°C, and the reaction was continued for 12h; the microspheres were centrifuged at 5000rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50mL concentrated sulfuric acid (98.3wt%), the temperature was raised to 80°C, and the reaction was continued for 8h; the microspheres were centrifuged at 5000rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface.

[0089] A total mass of 0.1 g of ferrous chloride heptahydrate and ferric chloride hexahydrate was mixed with 100 g of water in a mass ratio of 2:1 (the total mass of iron salts accounted for 10 wt% of the mass of blank polymer microspheres), and the above-obtained AIE polymer microspheres with sulfonated surfaces were added. After swelling reaction for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. This was repeated three times to obtain iron salt-chelated AIE polymer microspheres; 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salts reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres; the microspheres were centrifuged at 5000 rpm and resuspended in water. This was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0090] The morphology of the aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5 μm. The CV value of the flow fluorescence signal tested by an analytical flow cytometer was 4.5%, the CV value of the flow FCS was 5.6%, and the encoding peak was 10-fold, indicating successful encoding.

[0091] Example 5

[0092] Weigh 2.5 g of blank polymer microspheres and disperse them in 150 g of water. Add 5 mL of dichloromethane and swell for 30 min to obtain a microsphere dispersion.

[0093] 25mg AIE-6 molecules, 50mg AIBN, and 5g ethylene glycol dimethacrylate were dissolved in 5mL poly(glycidyl methacrylate) (the mass of AIE molecules accounted for 1wt% of the mass of blank polymer microspheres), and the microsphere dispersion was added; after swelling at room temperature for 8h, 250mg polyvinyl pyrrolidone was added, the temperature was raised to 70°C, and the reaction was continued for 12h; the microspheres were centrifuged at 5000rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 75mL concentrated sulfuric acid (98.3wt%), the temperature was raised to 80°C, and the reaction was continued for 8h; the microspheres were centrifuged at 5000rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface.

[0094] A total mass of 0.5 g of ferrous chloride heptahydrate and ferric chloride hexahydrate was mixed with 100 g of water in a mass ratio of 2:1 (the total mass of iron salts accounted for 20 wt% of the mass of blank polymer microspheres), and the above-obtained AIE polymer microspheres with sulfonated surfaces were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain iron-chelated AIE polymer microspheres. 75 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salts reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres. The microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0095] The morphology of the aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5 μm. The CV value of the flow fluorescence signal tested by an analytical flow cytometer was 3.3%, the CV value of the flow FCS was 4.7%, and the encoding peak was 10-fold, indicating successful encoding.

[0096] Example 6

[0097] Weigh 10 g of blank polymer microspheres and disperse them in 500 g of water. Add 10 mL of dichloromethane and swell for 30 min to obtain a microsphere dispersion.

[0098] 50mg AIE-9 molecules, 100mg AIBN, and 10g divinylbenzene were dissolved in 25mL styrene (the mass of AIE molecules accounted for 0.5wt% of the mass of blank polymer microspheres), and the microsphere dispersion was added; after swelling at room temperature for 10h, 500mg polyvinyl alcohol was added, the temperature was raised to 70°C, and the reaction was continued for 12h; the microspheres were centrifuged at 5000rpm and resuspended in water, and the process was repeated three times to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 100mL concentrated sulfuric acid (98.3wt%), the temperature was raised to 80°C, and the reaction was continued for 8h; the microspheres were centrifuged at 5000rpm and resuspended in water, and the process was repeated three times to obtain AIE polymer microspheres with sulfonated surfaces.

[0099] A total mass of 1 g of ferrous chloride heptahydrate and ferric chloride hexahydrate was mixed with 100 g of water in a mass ratio of 2:1 (the total mass of iron salts accounted for 10 wt% of the mass of blank polymer microspheres), and the above-obtained AIE polymer microspheres with sulfonated surfaces were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. This was repeated three times to obtain iron salt-chelated AIE polymer microspheres; 100 mL of 0.5 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salts reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres; the microspheres were centrifuged at 5000 rpm and resuspended in water. This was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0100] The morphology of the aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 7 μm. The CV value of the flow fluorescence signal tested by an analytical flow cytometer was 2.3%, the CV value of the flow FCS was 3.3%, and the encoding peak was 10-fold, indicating successful encoding.

[0101] Example 7

[0102] Weigh 0.1 g of blank polymer microspheres and disperse them in 12.5 g of water. Add 1 mL of chloroform and swell for 30 min to obtain a microsphere dispersion.

[0103] 10 mg of AIE-11 molecules (alkyl chain-C 6 H 13The AIE polymer microspheres were added to 15 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was repeated three times to obtain the AIE polymer microspheres. The obtained AIE polymer microspheres were added to 15 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was repeated three times to obtain the AIE polymer microspheres with sulfonation modification on the surface.

[0104] A total mass of 0.02g of ferrous chloride heptahydrate and ferric chloride hexahydrate was mixed with 10g of water in a mass ratio of 2:1 (the total mass of iron salt accounted for 20wt% of the mass of blank polymer microspheres), and the above-obtained AIE polymer microspheres with sulfonated surface were added. After soaking and reacting for 1h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain iron salt-chelated AIE polymer microspheres; 15mL of 1mol / L sodium hydroxide solution was added, the temperature was raised to 80℃, and the reaction was carried out for 2h. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres; the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0105] The fluorescence spectrum of the aggregation-induced luminescence magnetically encoded microspheres was tested using a fluorescence spectrometer, with an excitation wavelength of 485 nm and an emission wavelength of 615 nm. The morphology of the aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 6 μm. The CV value of the flow fluorescence signal tested using an analytical flow cytometer was 3.2%, the CV value of the flow FCS was 4.5%, the encoding peak was 10-fold, and the encoding was successful.

[0106] Example 8

[0107] Weigh 1 g of blank polymer microspheres and disperse them in 125 g of water, add mL of tetrahydrofuran and swell for 30 min to obtain a microsphere dispersion;

[0108] 25mg AIE-15 molecules, 30mg AIBN, and 5g divinylbenzene were dissolved in 5mL styrene (the mass of AIE molecules accounted for 2.5wt% of the mass of blank polymer microspheres), and the microsphere dispersion was added; after swelling at room temperature for 8h, 50mg polyvinyl alcohol was added, the temperature was raised to 70°C, and the reaction was continued for 12h; the microspheres were centrifuged at 5000rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50mL concentrated sulfuric acid (98.3wt%), the temperature was raised to 80°C, and the reaction was continued for 8h; the microspheres were centrifuged at 5000rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surfaces.

[0109] A total mass of 0.2 g of ferrous chloride heptahydrate and ferric chloride hexahydrate was mixed with 100 g of water in a mass ratio of 2:1 (the total mass of iron salts accounted for 20 wt% of the mass of blank polymer microspheres), and the above-obtained AIE polymer microspheres with sulfonated surfaces were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. This was repeated three times to obtain iron salt-chelated AIE polymer microspheres; 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salts reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres; the microspheres were centrifuged at 5000 rpm and resuspended in water. This was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0110] The morphology of the aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5.5 μm. The CV value of the flow fluorescence signal tested by an analytical flow cytometer was 5.2%, the CV value of the flow FCS was 2.5%, and the encoding peak was 10-fold, indicating successful encoding.

[0111] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.

Claims

1. An aggregation-induced luminescence magnetically encoded microsphere based on in-situ polymerization coating, characterized in that: Including AIE polymer microspheres and magnetic particles; The AIE polymer microspheres are obtained by embedding AIE molecules inside blank polymer microspheres through an in-situ polymerization coating method, wherein the amount of AIE molecules used in the in-situ polymerization coating method is 0.01-10wt% of the amount of blank polymer microspheres; the blank polymer microspheres are selected from at least one of polystyrene microspheres, polymethyl methacrylate microspheres and polyglycidyl acrylate microspheres; the in-situ polymerization coating method is to cause the AIE molecules, reactive monomers, initiators and cross-linking agents to undergo swelling polymerization reaction with the blank polymer microspheres in the dispersed phase of the reaction system so that the AIE molecules are embedded inside the blank polymer microspheres; The magnetic particles are deposited on the surface of the AIE polymer microspheres by an in-situ precipitation method of iron salts, wherein the amount of iron salts used in the in-situ precipitation method is 3-30wt% of the amount of blank polymer microspheres; the iron salts are a compound of trivalent iron salts and divalent iron salts; the in-situ precipitation method is to add an alkaline solution to the iron salts chelated with the surface of the AIE polymer microspheres to react in situ to generate magnetic particles deposited on the surface of the AIE polymer microspheres, and the surface of the AIE polymer microspheres is modified by sulfonation in the in-situ precipitation method.

2. The aggregation-induced luminescence magnetically encoded microspheres based on in-situ polymerization coating according to claim 1, characterized in that: The magnetic particles are Fe3O4; The ferric iron salt is selected from at least one of ferric chloride hexahydrate and anhydrous ferric chloride; the ferrous iron salt is selected from at least one of ferrous chloride tetrahydrate, ferrous chloride dihydrate, ferrous sulfate and ferrous sulfate heptahydrate; The AIE molecule is selected from at least one of the following AIE-1 molecules to AIE-16 molecules:

3. The aggregation-induced luminescence magnetically encoded microspheres based on in-situ polymerization coating according to claim 1, characterized in that: In the in-situ polymerization coating method, the reactive monomer is selected from at least one of styrene, glycidyl methacrylate and isocyanoethyl methacrylate, the initiator is selected from at least one of azobisisobutyronitrile, dibenzoyl peroxide, azobisisovaleronitrile, cumene hydroperoxide and azobisisoheptylonitrile, and the crosslinking agent is selected from at least one of divinylbenzene, ethylene glycol dimethacrylate, diisocyanate and N,N-methylenebisacrylamide; the particle size range of the blank polymer microspheres is 0.03 μm to 50 μm; In the in-situ precipitation method, the alkaline solution is selected from at least one of sodium hydroxide solution, ammonia water, potassium hydroxide solution and sodium bicarbonate solution.

4. The aggregation-induced luminescence magnetically encoded microspheres based on in-situ polymerization coating according to claim 1, characterized in that: In the in-situ polymerization coating method, the mass amount of the AIE molecule is 0.001% to 10% of the mass amount of the reactive monomer, the mass amount of the initiator is 0.1% to 10% of the mass amount of the reactive monomer, and the mass amount of the crosslinker is 1% to 50% of the mass amount of the reactive monomer.

5. The aggregation-induced luminescence magnetically encoded microspheres based on in-situ polymerization coating according to claim 1, characterized in that: The CV value of the flow fluorescence signal and the CV value of the flow FCS of the aggregation-induced luminescence magnetic encoding microspheres based on in-situ polymerization coating are both less than 10%, and the encoding peak is ≥10.

6. The method for preparing aggregation-induced luminescence magnetically encoded microspheres based on in-situ polymerization coating according to any one of claims 1 to 5, characterized in that: The steps include: S1. Preparation of AIE polymer microspheres by in situ polymerization and coating Dispersing blank polymer microspheres in water, adding a swelling agent to swell the microspheres to obtain a microsphere dispersion; AIE molecules, initiators and crosslinkers are dissolved in reactive monomers, and microsphere dispersion is added. After swelling reaction, stabilizers are added, and the swelling agent is removed by heating. The supernatant is removed by centrifugation to obtain AIE polymer microspheres. S2. Preparation of Aggregation-Induced Luminescence Magnetic Encoded Microspheres Based on In-situ Polymerization and Coating by In-situ Precipitation The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is increased for reaction, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation-modified surfaces. The microspheres are mixed with iron salt and water for reaction, and the supernatant is removed by centrifugation to obtain iron salt-chelated AIE polymer microspheres. An alkaline solution is added, and the temperature is increased. The iron salt reacts in situ to generate magnetic particles that are deposited on the surface of the AIE polymer microspheres. The supernatant is removed by centrifugation to prepare aggregation-induced luminescence magnetically encoded microspheres based on in situ polymerization coating.

7. The method for preparing aggregation-induced luminescence magnetically encoded microspheres based on in-situ polymerization coating according to claim 6, characterized in that: The following steps are involved: S1. Preparation of AIE polymer microspheres by in situ polymerization and coating Dispersing blank polymer microspheres in water, adding a swelling agent to swell the microspheres for 0.1 to 6 hours to obtain a microsphere dispersion; AIE molecules, initiators and crosslinkers are dissolved in reactive monomers, and microsphere dispersion is added. After swelling reaction for 0.5 to 6 hours, a stabilizer is added, and the temperature is raised to 60°C to 100°C for reaction for 2 to 12 hours to remove the swelling agent, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres. S2. Preparation of Aggregation-Induced Luminescence Magnetic Encoded Microspheres Based on In-situ Polymerization and Coating by In-situ Precipitation The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is increased to 30°C to 100°C and the reaction is carried out for 4 to 12 hours, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation modified on the surface. The microspheres are mixed with iron salt and water, and the mixture is immersed in the solution for reaction for 0.5 to 10 hours, and the supernatant is removed by centrifugation to obtain iron salt-chelated AIE polymer microspheres. An alkaline solution is added, and the temperature is increased to 40°C to 120°C and the reaction is carried out for 0.5 to 4 hours. The iron salt reacts in situ to generate magnetic particles which are deposited on the surface of the AIE polymer microspheres, and the supernatant is removed by centrifugation to prepare aggregation-induced luminescence magnetically encoded microspheres based on in situ polymerization coating.

8. The method for preparing aggregation-induced luminescence magnetically encoded microspheres based on in-situ polymerization coating according to claim 6, characterized in that: In step S1, the mass amount of blank polymer microspheres in the microsphere dispersion is 0.1% to 20% of the mass amount of water, and the mass amount of the swelling agent is 0.05% to 40% of the mass amount of water; the swelling agent is selected from at least one of dichloromethane, tetrahydrofuran, chloroform, anisole, benzyl alcohol and toluene; In step S1, the mass amount of the stabilizer is 0.01% to 5% of the mass amount of water; the stabilizer is selected from at least one of polyvinyl pyrrolidone and polyvinyl alcohol; In step S2, the mass concentration of the sulfuric acid solution is 70% to 99%; the mass amount of the AIE polymer microspheres is 1% to 30% of the mass amount of the sulfuric acid solution; In step S2, the mass dosage of the iron salt is 0.0005% to 25% of the mass dosage of water; the mass dosage of the alkaline solution is 0.1% to 50% of the mass dosage of water; the mass concentration of the alkaline solution is 1% to 10%; The water in step S1 and step S2 is ultrapure water; the centrifugal speed is 3000 rpm to 6000 rpm, the centrifugal time is 5 min to 60 min, and the number of centrifugation is more than three times.

9. Use of the aggregation-induced luminescence magnetically encoded microspheres based on in situ polymerization coating as claimed in any one of claims 1 to 5 as core raw materials of protein biochips in in vitro non-disease diagnosis and detection.

Citation Information

Patent Citations

  • Method for preparing superparamagnetic microspheres with surfactant-based nuclear shell

    CN108467461A

  • Aggregation-induced emission magnetic fluorescent coding microsphere, preparation method and application thereof

    CN108587610A